Formulation And Antibacterial Activity Test Of Betel Leaf (Piper Betle L.) Essential Oil Mouthwash Against Streptococcus mutans - Prasti Andini; Anisa Firdaus; Novita Diana Ayu Candra; Nina Salamah; Sri Mulyaningisih (Universitas Wahid Hasyim Semarang, 2026)
Dental caries is a prevalent oral health issue in Indonesia, largely caused by Streptococcus mutans. While Piper betle L. essential oil possesses known antibacterial properties, its utilization in a stable mouthwash formulation requires scientific validation. Objective: This study aimed to formulate Piper betle L. essential oil into a mouthwash emulsion and evaluate its antibacterial activity against S. mutans. Essential oil was obtained via steam distillation and formulated into mouthwashes at concentrations of 1%, 2%, and 4% (v/v) using Tween 80 as an emulsifier. Antibacterial activity was assessed using the well-diffusion method against S. mutans (0.5 McFarland standard) in independent triplicate wells (n=3). Vehicle control (without essential oil) and Povidone-Iodine 10% (positive control) were used for comparison. Data were analyzed using One-Way ANOVA followed by Tukey HSD post-hoc test (p<0.05). The formulation containing 4% essential oil exhibited the strongest antibacterial activity among the test groups, with an inhibition zone of 12.66 ± 1.76 mm, which was significantly higher than the vehicle control (9.29 ± 2.67 mm; p < 0.05). The positive control showed the highest inhibition (18.03 + 1.16 mm). Physical evaluation confirmed that all formulations remained stable during 7 days of storage at room temperature (27 ± 2°C), with no specific control of relative humidity, with pH values (6.46–6.82) and specific gravity (1.03–1.04 g/mL) within physiological limits. Piper betle L. essential oil mouthwash is physically stable and effective against S. mutans in a concentration-dependent manner, suggesting its promising potential as a natural alternative for oral hygiene maintenance